Occupational risk assessment in a large-scale road maintenance and conservation work using the FMEA: an investigation on signaling and road work - Lima, Ailda da Luz; Uchoa, Jhelison Gabriel Lima; Cavaignac, André Luís de Oliveira (Brazilian Journal of Production Engineering, 2021)
The constant rise of the road modal is indisputable in the same way that it is the most representative in transport logistics in Brazil. Due to the increased use of this medium too much, the demand for services in construction, maintenance and conservation works has grown. These activities have high labor risks, and the problem with this growth lies in the safety of the work of those who operate on the roads.  In this sense, the objective of this research is to investigate of the situation of construction workers in large construction work - maintenance and conservation of highway, stretch of Açailândia-MA to Imperatriz-MA, with emphasis on the processes of slapping hole and cleaning drainage devices. Through the photographic records, a discussion was conducted about the non-conformities found in comparison to regulatory standards nº 6 - Personal Protective Equipment (PPE) and nº 18 - Safety Measures. Subsequently, the data obtained were used as probable modes of failures, through the situations analyzed for the application of FMEA (failure mode and effect analysis). With the obtaining of the RPN (risk priority number) it was possible to organize the failure modes in order of priority, from the riskiest to the least risky. For cleaning service made with a manual brush cutter, the failure of the safety system suitable for the equipment had the highest RPN of 210, also the highest general RPN, followed by the Traffic Accident failure mode with the cause of non-signaling on the stretch of the work obtained 108 RPN. Therefore, presents itself a plan of preventive actions in order to contribute to mitigate the occupational risks present in the researched work.
Keywords: Highways, Occupational Safety, Risks, FMEA.